Mediterranean Resonances in Tolkien’s Middle-earth - Lukić, Mina D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper examines the influences of Mediterranean heritage on the shaping of the culture of Gondor and more specifically on the appearance of its capital, Minas Tirith, as described by J. R. R. Tolkien, and portrayed in Peter Jackson’s film adaptations of The Lord of the Rings. By tracing the similarities between Númenor and Gondor and the ancient and mediaeval civilisations they resemble, and by analysing the sources from the history of art which inspired the designs of Minas Tirith’s architecture, the paper aims to demonstrate the interplay and transfer of meanings and cultural connotations from real to fictional places and cultures.
Keywords: J.R.R. Tolkien; The Lord of the Rings; Númenor; Gondor; Minas Tirith; architecture as cultural signifier; uses of heritage